A rare case of herpes zoster maxillaris with cranial polyneuropathy - Patro, Shubhransu; Sahoo, Debananda; Dash, Anil Kumar; Mishra, Biswamohan (International Journal of Advances in Medicine, 2017)
Varicella zoster virus has a high affinity for the ganglion and causes various neuropathies. About 12% of all peripheral facial nerve palsies are caused by varicella zoster virus, a rare complication due to reactivation of the herpes zoster virus in the geniculate ganglion of facial nerve. The occurrence rate of associated cranial polyneuropathy has been reported to be 1.8-3.2% and cranial nerves VII, VIII, IX and X are the ones most commonly affected. Here, we present a case of Herpes zoster maxillaris with cranial polyneuropathy who was improved with oral anti-viral drugs and steroid. Multiple cranial nerve palsies are being observed frequently in patients who were referred with a preliminary diagnosis of facial palsy. These patients are required to be examined in detail for involvement of other cranial nerves. Early diagnosis and treatment is required for reversing the functions of cranial nerves and decreasing the chance of developing other complications.